2020
DOI: 10.1038/s41598-020-76314-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sound levels and patient-related factors on sleep of patients in the intensive care unit: a cross-sectional cohort study

Abstract: Sleep disruption is common in patients in the intensive care unit (ICU). The aim of the study was to measure sound levels during sleep-protected time in the ICU, determine sources of sound, assess the impact of sound levels and patient-related factors on duration and quality of patients' sleep. The study was performed between 2018 and 2019. A commercially available smartphone application was used to measure ambient sound levels. Sleep duration was measured using the Patient's Sleep Behaviour Observational Tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…Fourthly, the noise that imitates engine sound was not examined. Listening to music is a widely used tool to improve sleep [32], whereas sound levels are negatively correlated with sleep duration in patients in an intensive care unit [33]. Finally, the applicability of results to real-life situations is limited due to the selection of people with good sleep and health in the present experiments.…”
Section: Discussionmentioning
confidence: 93%
“…Fourthly, the noise that imitates engine sound was not examined. Listening to music is a widely used tool to improve sleep [32], whereas sound levels are negatively correlated with sleep duration in patients in an intensive care unit [33]. Finally, the applicability of results to real-life situations is limited due to the selection of people with good sleep and health in the present experiments.…”
Section: Discussionmentioning
confidence: 93%
“…Literature studies report average noise values between 46 and 66 dBA, with peaks between 59 and 91 dBA, both in general, surgical, and even SARS-COVID-19 dedicated ICUs, far exceeding the noise levels recommended for hospitals. 10,18,[27][28][29][30][31][32][33][34] Medical devices produce lowfrequency and repetitive sounds, resulting in unavoidable noise 24 h a day. Moreover, most of the noise in the ICU is generated from sources immediately adjacent to the patient's ears, maximizing its adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…These results support those of Simons et al (2018), who found that noise volume negatively correlated with ICU patients’ self-reported sleep quality [ 30 ]. Further, Czempik et al (2020) found that ICU noise volume was negatively correlated with patients’ sleep time and quality, with 17% of respondents reporting that environmental noise was the main factor affecting their sleep quality [ 31 ]. Chaudhary et al (2020) found that 76.6% of ICU patients ( n = 60) experienced poor sleep and that pain (33.3%), noise (31.7%), and light (3.3%) were the most critical factors [ 32 ].…”
Section: Discussionmentioning
confidence: 99%